Implementing Public Expenditure Tracking Surveys for Results : Lessons from a Decade of Global Experience - Gurkan, Asli; Kaiser, Kai; Voorbraak, Doris (World Bank, Washington, DC, 2012)
Public Expenditure Tracking Surveys (PETS) can serve as a powerful tool to inform prevailing public financial management (PFM) practices and the extent to which government budgets link to execution and desired service delivery objectives and beneficiaries. Since the first PETS in Uganda in 1996, tracking exercises have now been conducted in over two dozen other countries, often as part of core analytical and advisory work related to PFM. This note synthesizes the findings and lessons from a number of recent PETS stocktaking exercises and indicates their potential benefits for enriching PFM and sectoral policy dialogues in a variety of country settings. Key findings include: (i) PETS have proven to be useful as part of a broader policy strategy aimed at improving service delivery results; (ii) PETS has become a brand name for very different instruments, but at its core there is a survey methodology that requires skilled technical expertise and a solid knowledge of budget execution processes; (iii) policy impact in a variety of PETS experiences could be further strengthened by stronger country ownership and effective follow-up; and (iv) the Bank could enhance PETS results through strategic partnering, and greater emphasis on dissemination and communication strategies aimed at involving actors who can foster actions on the ground.